TRADISI REBO KASAN SEBAGAI PENDEKATAN BERBASIS MASYARAKAT DALAM MENJAGA EKOLOGI PANTAI SIANGAU DESA TELUK LIMAU - Shoddiq Munjiuz Zaman; Nico Oktario Adytyas (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
This article examines the role of local wisdom in the village of Teluk Limau, particularly in the Rebo Kasan tradition, which contributes to maintaining the ecology of Pantai Siangau.The Rebo Kasan tradition, performed on the last Wednesday of the month of Safar, is a ritual to ward off misfortune that has been preserved by the local community to maintain ecological balance, strengthen social identity, and enhance solidarity among residents.Besides being a cultural ritual, Rebo Kasan has also become a tourist attraction that benefits the local economy.This research applies a qualitative approach with a descriptive method, relying on both primary and secondary data sources.Primary data were obtained through interviews with the village chief and 2 community members of Teluk Limau Village, while secondary data were taken from various relevant literature.Data were obtained through observation, interviews, and documentation methods.The findings of this research indicate that the implementation of the Rebo Kasan tradition strengthens social relationships among residents and helps preserve coastal ecosystems while raising awareness of environmental sustainability.The community collectively works together to maintain beach cleanliness and integrates social, economic, and environmental principles into sustainability practices.The Rebo Kasan tradition also increases community income and introduces local wisdom to tourists, demonstrating cultural and ecological sustainability that can be emulated by other communities.This research concludes that Rebo Kasan is an important example of the integration of culture, ecology, and economy in sustainable development that supports the preservation of cultural heritage.